2022
DOI: 10.1186/s12969-021-00657-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of chronic nonbacterial osteomyelitis in children: a multicenter case series

Abstract: Objective The aim of this study was to evaluate demographic, clinical, laboratory, imaging, histopathology characteristics, and treatment responses of children with Chronic nonbacterial osteomyelitis (CNO). Methods Retrospective multi-center case series study of pediatric patients diagnosed with CNO treated at five tertiary centers in south China. Results Totally there were 18 patients diagnosed as CNO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In cases of more severe CRMO, instead of first-line medicaments, NSAIDs or, in combination with them, a wide range of second-line treatment options is available, including disease-modifying anti-rheumatic drugs (DMARDs), glucocorticoids and bisphosphonates [ 25 , 26 ]. Pamidronate, classified as a nitrogen-containing bisphosphonate, inhibits farnesyl diphosphate synthase in osteoclasts by mimicking its substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of more severe CRMO, instead of first-line medicaments, NSAIDs or, in combination with them, a wide range of second-line treatment options is available, including disease-modifying anti-rheumatic drugs (DMARDs), glucocorticoids and bisphosphonates [ 25 , 26 ]. Pamidronate, classified as a nitrogen-containing bisphosphonate, inhibits farnesyl diphosphate synthase in osteoclasts by mimicking its substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports suggest that the bisphosphonates offer promising efficacy in controlling CRMO, as well as safety of use [ 16 , 28 ], though results of recent studies indicated a burden of adverse events (AEs) in pamidronate therapy. In some patients, bisphosphonates were found to worsen bone pain [ 25 ], as well as lead to nausea, headache, fever and phlebitis [ 29 ], which ultimately decrease patients’ compliance [ 30 ]. The presented patient’s therapy was well tolerated and led to no significant AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports of spinal involvement in CNO/CRMO were considered rare in the literature, but in the last 20 years there has been a gradual increase with an incidence of approximately 10%-38% (3,(10)(11)(12)(13). We reviewed the vertebral involvement of CNO/ CRMO patients in the literature since 2000 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The data shown for bisphosphonates in Table 1[37 ▪▪ ,38 ▪ ,39,40,41 ▪ ,42 ▪ ,43 ▪ ,44,45,46,47 ▪▪ ] and TNFi in Table 2[37 ▪▪ ,38 ▪ ,39,40,41 ▪ ,42 ▪ ,43 ▪ ,44,45,47 ▪▪ ,48 ▪ ] demonstrates the difficulty of comparing retrospective outcome studies. The dosing regimens were different, and some studies used clinical outcomes measures while others reported imaging outcomes.…”
Section: Recent Reports Of Treatment Responsesmentioning
confidence: 99%